Management of the Oral Health of Children During the COVID-19 Pandemic in Poland - Olszewska, Aneta; Paszynska, Elzbieta; Roszak, Magdalena; Czajka-Jakubowska, Agata (Frontiers in Public Health, 2021)
During COVID-19 pandemic, managing children's oral health represents specific problems; defining highly effective infection control protocols in a dental setting and to implement specific treatment protocols are of fundamental importance. The aim of this study was, to present the risk factors associated with pediatric dental treatment and management of emergency and non-emergency cases in the Wielkopolska region of Poland. The research was based on data from the Regional National Health Fund relating the oral health management of children aged 0-18 in the pandemic period of 2020. Categorical data were analyzed with the Chi-square test and/or as the difference between two proportions (p<0.05). The results showed statistical differences in the number of performed procedures when comparing 2019 and 2020; especially in April, when lockdown restrictions reached their highest level and when only 30% of dental clinics were open for children. Statistical analysis revealed changes in the profile of clinical situations that represented emergency cases and pandemic treatment protocols.